Synthesis, Structural Characterization, Thermal and Biological Studies of Some Metal Complexes with Aroyl Hydrazone Based Ligand - Aswar, A.S.; Thakare, K.A. (Asian Journal of Chemistry, 2020)
The metal complexes of Ti(III), Cr(III), Fe(III), VO(IV), MoO2(VI), WO2(VI), Th(IV) have been synthesized with hydrazone ligand. The mononucleating hydrazone ligand has been synthesized via condensation reaction between pyrazine-2-carbohydrazide and 2,4-dihydroxy benzophenone in 1:1 ratio. The ligand and its complexes were studied on the basis of elemental analysis, magnetic susceptibility measurements, IR and electronic spectra, TGA, XRD, 1H NMR, mass spectroscopy and SEM analysis. Spectroscopic and magnetic studies suggest coordination of most of the metal complexes in a regular octahedral around the central metal ions except vanadium which is square pyramidal. Free ligand as well as its metal complexes were screened against the growth of pathogenic bacteria. The inhibition data revealed that metal complexes exhibit higher inhibition potential against growth of bacteria and fungi than free ligand.